CT and MRI findings of ameloblastoma in two cases - Cihangiroglu, M; Akfirat, M; Yildirim, H (Springer-Verlag, 2002)
We report CT and MRI findings in two patients with ameloblastoma. One case had a multilocular mixed lesion and the other had a unilocular solid pattern. The second case is probably one of the youngest reported. CT and MRI can be used to delineate and show the extent of the tumour.
Keywords: ameloblastoma, jaw; computed tomography; magnetic resonance imaging